Assessment of essential communicative skills of first year medical students - Ivanchenko, O. Z; Melnikova, O. Z.; Lurie, K. I.; Іванченко, Олена Зенонівна; Мельнікова, Оксана Зенонівна; Лур'є, Костянтин Ігорович (My University, 2021)
The purpose of the presented work is to assess the development and progression of basic communication skills of the 1st year students of the medical faculty that can serve as the basis for their further improvement over the course of professional education. The general level of students' communication skills was assessed using the test "Diagnosis of communicative and organizational tendencies"; the general level of empathy and the degree of its manifestation in communicating with different categories of people were studied using the Yusupov I. test; types of behavior in conflicts were estimated using the Thomas test. The research findings were processed according to the keys suggested by the authors of the tests. The study has shown that the majority of students (66%) demonstrates a high and very high level of general communication, while 18% of participants have low and very low levels of communication skills. An adequate general level of empathy was found in 91.7% of 1st year students, moreover, it was high in the remaining 8.3% of students. All respondents have shown the greatest empathy towards parents (average level 10.1 out of 15 possible scores), strangers (9.2) and children (8.9), while the level of empathy for older people was 6.9 points. Determining the strategy for resolving conflict situations has revealed that 1st year students most often choose a compromise (22.5% boys and 24% girls), the strategy of avoidance ranks the second position and is commn among the girls (23%, while the boys exhibit rivalry (21.8%), cooperation is chosen mainly by the girls (19.8%). The results of the study have shown that high levels of general communication and empathy could contribute to the choice of a future profession by the students and need only the right support during their graduate training program. Much attention should be paid to fostering empathy for the elderly people and the choice of cooperation as the best conflict resolution strategy between the parties during educational process at the university. Метою представленої роботи було дослідження у студентів 1 курсу медичного факультету рівня сформованості основних комунікативних навичок, що може служити основою їх подальшого розвитку в ході подальшого навчання. Загальний рівень комунікативності студентів оцінювали, використовуючи тест «Діагностика комунікативних і організаторських схильностей», рівень емпатії і ступінь її прояву в спілкуванні з різними категоріями людей і в поводженні з тваринами вивчали за допомогою тесту Юсупова І.М., типи поведінки в конфліктах, застосувавши тест Томаса. Результати дослідження оброблені згідно ключам, які запропоновані авторами тестів. Показано, що більшість студентів (66%) мали високий і дуже високий рівень загальної комунікативної, тоді як низький і дуже низький - лише 18%. Нормальний загальний рівень емпатії виявлено у 91,7% першокурсників, а у решти 8,3% учнів він виявився високим. Найбільшу емпатію студенти проявляли до батьків (середній рівень 10,1 з 15 можливих балів), незнайомцям (9,2) і дітям (8,9), тоді як до людей похилого віку рівень емпатії склав 6,9 балів. Визначення стратегії вирішення конфліктних ситуацій показало, що найчастіше першокурсники вибирали компроміс (22,5% хлопців і 24% дівчат), на другому місці у дівчат було уникнення (23%), а у хлопців - суперництво (21,8%). Співпрацю було вибрано, в основному, дівчатами (19,8%). Результати дослідження показали, що високі рівні загальної комунікації і емпатії могли сприяти вибору майбутньої професії студентами і потребують в ході їх подальшого навчання тільки правильної підтримки, тоді як емпатію до літніх людей і, особливо, вибір найкращої стратегії вирішення конфліктів у вигляді співробітництва сторін необхідно значною мірою формувати і розвивати протягом освітнього і виховного процесів в університеті.
Рівень сформованості основних комунікативних навичок у студентів першого курсу медичного факультету
Keywords: 1st year students; communication; empathy; conflict situations; першокурсник; комунікація; емпатія; конфліктні ситуації